PDTM-28. AN OTX2-PAX3 SIGNALLING AXIS REGULATES GROUP 3 MEDULLOBLASTOMA CELL FATE. (11th November 2019) - Zagozewski, Jamie; Shahriary, Ghazaleh; Morrison, Ludivine; Stromecki, Margaret; Fresnoza, Agnes; Palidwor, Gareth; Porter, Christopher; Forget, Antoine; Ayrault, Olivier; Hawkins, Cynthia; Chan, Jennifer; Saulnier, Olivier; et al.
Abstract: The majority of Group 3 medulloblastomas (MB) exhibit amplification or increased expression of OTX2. OTX2 is primarily known as an oncogenic driver of tumor growth and cell cycle progression in Group 3 MB; however, its role as a repressor of differentiation is poorly characterized. Therefore, we utilized extensive patient data and mapped Group 3 MB chromatin dynamics in stem cell-enriched cultures to evaluate the divergent role of OTX2 in cell fate decisions in Group 3 MB pathogenesis. Several PAX genes were identified as novel OTX2 targets in Group 3 MB. Examination of patient data revealed that PAX3 and PAX6 expression is significantly reduced in Group 3 MB patients and is associated with significantly reduced survival. Functional evaluation of PAX3 and PAX6 expression showed that PAX3 expression significantly reduced self-renewal capacity of Group 3 MB tumorspheres in vitro and significantly prolonged survival and reduced tumor size in orthotopic xenograft models in vivo . RNA-sequencing of PAX3 and PAX6 gain of function (GOF) tumorspheres revealed mTORC1 signalling was specifically downregulated in PAX3 GOF, indicating this pathway may be critical for the survival and self-renewal differences observed between PAX3/PAX6 GOF models. Treatment of Group 3 MB with mTOR inhibitors reduced self-renewal in vitro and significantly prolonged survival and reduced tumor size in vivo . To further evaluate the role for this signalling axis in the Group 3 MB neural lineage hierarchy, we carried out scRNA-sequencing in tumorspheres from 4 Group 3 MB cell lines. Interestingly, a broad range of OTX2 expression was observed across single cell clusters, suggesting distinct OTX2 regulatory hierarchies are present in Group 3 MB. Collectively, our work demonstrates the multifaceted role of OTX2 as a regulator of cell fate decisions in Group 3 MB and identifies a novel role for mTORC1 signalling in Group 3 MB self-renewal and differentiation.